2015
DOI: 10.1128/ec.00170-14
|View full text |Cite
|
Sign up to set email alerts
|

The Hsp90 Cochaperones Cpr6, Cpr7, and Cns1 Interact with the Intact Ribosome

Abstract: The abundant molecular chaperone Hsp90 is essential for the folding and stabilization of hundreds of distinct client proteins. Hsp90 is assisted by multiple cochaperones that modulate Hsp90's ATPase activity and/or promote client interaction, but the in vivo functions of many of these cochaperones are largely unknown. We found that Cpr6, Cpr7, and Cns1 interact with the intact ribosome and that Saccharomyces cerevisiae lacking CPR7 or containing mutations in CNS1 exhibited sensitivity to the translation inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…Notably, the first segment with helical propensity revealed by NMR coincides with the region that conveys the essential function of Cns1 identified in our viability assay. Several previous studies reported a functional overlap between Cns1 and Cpr7 in vivo (Marsh et al, 1998;Tenge et al, 2015;Tesic et al, 2003;Zuehlke and Johnson, 2012), but the nature of this genetic interaction was not clear. Moreover, both proteins were reported to weakly interact with the 80S ribosome (Albanè se et al, 2006;Tenge et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Notably, the first segment with helical propensity revealed by NMR coincides with the region that conveys the essential function of Cns1 identified in our viability assay. Several previous studies reported a functional overlap between Cns1 and Cpr7 in vivo (Marsh et al, 1998;Tenge et al, 2015;Tesic et al, 2003;Zuehlke and Johnson, 2012), but the nature of this genetic interaction was not clear. Moreover, both proteins were reported to weakly interact with the 80S ribosome (Albanè se et al, 2006;Tenge et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…The cns1 and cpr7 mutant strains are known to be hypersensitive to the translation inhibitor hygromycin B (Albanè se et al., 2006;Tenge et al, 2015). Cns1 overexpression reverts this effect in the cpr7D strain ( Figure 4A).…”
Section: Cns1 and Cpr7 Play A Role In Translation Elongationmentioning
confidence: 95%
See 1 more Smart Citation
“…38 Although normal growth and full Hsp90 activity require Cpr7p, they do not require Cpr7p PPIase activity. 44 Intriguingly, yeasts lacking any components of the ribosome-associated complex (Ssb, Ssz1, and Zuo1) exhibit cold-sensitive growth. 39 The PPIase domain is suggested to mediate protein-protein interactions; thus, it may play a chaperoning role.…”
Section: Articlementioning
confidence: 99%
“…In addition, Cpr7 deletion resulted in a significant impairment of cell division (Duina et al 1996a). Both Cpr6 and Cpr7 interact with the ribosome and may be involved in the regulation of protein synthesis (Tenge et al 2015). …”
Section: Co-chaperonesmentioning
confidence: 99%